2022
DOI: 10.36348/jaspe.2022.v05i06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flossing Bands on Pain and Perceived Level of Function in Collegiate Baseball Pitchers

Abstract: Background: Tissue flossing bands are a relatively new treatment modality that have increased in popularity in recent years. There is evidence suggesting that tissue flossing could decrease pain and increase joint range of motion, but there is still a need for further studies in this matter. Thus, this study aimed to assess the effect of a single tissue flossing treatment on the perceived pain and upper extremity function among healthy collegiate baseball pitchers. Methods: Twenty apparently healthy collegiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Flossing application is a relatively recent technique involving compression bandaging typically for limb joints and has garnered attention in the realm of knee pathology treatment. Previous research reported that floss band application can significantly improve joint range of motion and reduce pain in individuals with knee arthritis [10], knee extensor maximum voluntary contraction torque [11], and significantly reduce perceived pain among athletes [12]. However, although flossing band therapy shows promise for knee pathology, evidence suggests that its long-term effectiveness remains to be conclusively determined [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flossing application is a relatively recent technique involving compression bandaging typically for limb joints and has garnered attention in the realm of knee pathology treatment. Previous research reported that floss band application can significantly improve joint range of motion and reduce pain in individuals with knee arthritis [10], knee extensor maximum voluntary contraction torque [11], and significantly reduce perceived pain among athletes [12]. However, although flossing band therapy shows promise for knee pathology, evidence suggests that its long-term effectiveness remains to be conclusively determined [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Our study hypothesizes that incorporating flossing band therapy into conventional physiotherapy for patients with Patellofemoral Pain Syndrome (PFPS) will result in more significant improvements in pain reduction, functional ability, and overall patient satisfaction compared to conventional physiotherapy alone. This hypothesis is predicated on the potential of flossing bands to enhance blood flow, reduce muscular tightness, and improve joint mobility, thereby augmenting the efficacy of standard physiotherapeutic techniques [11,12,14].…”
Section: Introductionmentioning
confidence: 99%